The secret that can't be hidden - Crews, Caitlin (Crews, Caitlin. Rich, ruthless & Greek, 2021)
"Kendra Connolly has never forgotten her first, fleeting encounter with billionaire Balthazar Skalas. When they meet again, she gives in to temptation--completely. It's a decision made in the heat of the moment that has life-changing consequences... Balthazar didn't expand his empire by being weak. The need he feels for Kendra is a liability, and the discovery that she's carrying his heir merely increases her power over him. Can this ruthless Greek be strong enough to let himself love her?"--Back cover.